1997
DOI: 10.1016/s0092-8674(00)80216-0
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylases and SAP18, a Novel Polypeptide, Are Components of a Human Sin3 Complex

Abstract: An important event in gene expression is the covalent modification of histone proteins. We have found that the mammalian transcriptional repressor Sin3 (mSin3) exists in a complex with histone deacetylases HDAC1 and HDAC2. Consistent with the observation that mSin3-mediated repression of transcription involves the modification of histone polypeptides, we found that the mSin3-containing complex includes polypeptides that tether the mSin3 complex to core histone proteins. In addition, two novel mSin3-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
483
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 533 publications
(504 citation statements)
references
References 43 publications
19
483
2
Order By: Relevance
“…reported activation by Myc (rather than repression) and the presence of a Myc binding site with regulatory region. a Bush et al, 1998; Boyd and Farnham, 1997;Boyd et al, 1998;c As noted in the text, Myc,Max dimers have been reported to bind an MrDb pseudogene in vivo Grandori et al, 1996;d Tavtigian et al, 1994;Tsuneoka et al, 1997; Grandori et al, 1996;f Tavtigian et al, 1994;Shim et al, 1997; Eilers et al, 1991;h Galaktionov et al, 1996;i Weihua et al, 1997;j Tsuneoka et al, 1997;k Reisman et al, 1993;Tavtigian et al, 1994;l Miltenberger et al, 1995; (Hassig et al, 1997;Laherty et al, 1997;Zhang et al, 1997;Sommer et al, 1997).…”
Section: Trrap Links Myc Transactivation To Chromatin Remodeling and mentioning
confidence: 95%
“…reported activation by Myc (rather than repression) and the presence of a Myc binding site with regulatory region. a Bush et al, 1998; Boyd and Farnham, 1997;Boyd et al, 1998;c As noted in the text, Myc,Max dimers have been reported to bind an MrDb pseudogene in vivo Grandori et al, 1996;d Tavtigian et al, 1994;Tsuneoka et al, 1997; Grandori et al, 1996;f Tavtigian et al, 1994;Shim et al, 1997; Eilers et al, 1991;h Galaktionov et al, 1996;i Weihua et al, 1997;j Tsuneoka et al, 1997;k Reisman et al, 1993;Tavtigian et al, 1994;l Miltenberger et al, 1995; (Hassig et al, 1997;Laherty et al, 1997;Zhang et al, 1997;Sommer et al, 1997).…”
Section: Trrap Links Myc Transactivation To Chromatin Remodeling and mentioning
confidence: 95%
“…A cDNA fragment confirmed to represent T-plastin 24 was cloned from a liver cDNA library. 25 The IMAGE cDNA clone 201315 (GenBank accession number R99689), corresponding to Sin3-associated polypeptide 18 kDa (SAP18), 26 and a cDNA fragment (GenBank accession number X89832), corresponding to mitochondrial DNA for loop attachment sequence, 27 were purchased from the American Type Culture Collection (Manassas, VA). Finally, to evaluate the amounts of RNA loaded, the filters were hybridized to kinaselabeled oligonucleotides specific for human 18S rRNA or a conserved sequence of 28S rRNA.…”
Section: Differential Display Analysismentioning
confidence: 99%
“…Indeed SMRT and N-CoR interact strongly with unliganded receptors and are released upon ligand binding. A series of recent reports (Alland et al, 1997;Hassig et al, 1997;Heinzel et al, 1997;Kadosh and Struhl, 1997;Laherty et al, 1997;Zhang et al, 1997) have shown that SMRT/ N-CoR co-repressors are part of a multiprotein complex including the Mad co-repressors mSin3A and B (Ayer et al, 1995;Schreiber-Agus et al, 1995) and the histone deacetylases HDAC1/HD1 and HDAC2/mRPD3 (Taunton et al, 1996;Yang et al, 1996). These studies, that strengthen the major role of histone acetylation/deacetylation in transcriptional regulation, provide the basis for the existence of a common repression pathway between nuclear receptors and basic region-helix ± loop ± helix-leucine zipper (bHLH-Zip) proteins.…”
Section: Introductionmentioning
confidence: 99%